Establishment of an indirect ELISA method for detecting bovine coronavirus antibodies based on N protein - Liu, Qiang; Niu, Xiaoxia; Jiang, Lingling; Zhang, Gang; Wang, Pu; Zhang, Sinong; Gao, Weifeng; Guo, Huichen; Wang, Yujiong; Li, Yong (Frontiers in Veterinary Science, 2025)
Bovine Coronavirus (BCoV) is a significant pathogen responsible for neonatal calf diarrhea, winter dysentery in adult cattle, and bovine respiratory diseases. Infection with the virus can result in hemorrhagic diarrhea, decreased milk production, and potentially fatal outcomes in cattle, leading to considerable economic repercussions for the cattle industry. Efficient management of BCoV relies on swift and precise detection techniques. CHO cells were utilized to express a secreted recombinant nucleocapsid protein (N), whereby rabbit polyclonal antibodies (pAb) were generated through immunization. An indirect enzyme-linked immunosorbent assay (iELISA) based on N protein was established for the detection of BCoV antibodies. Reaction conditions were optimized using a checkerboard approach, with the optimal antigen concentration at 1.25 μg/mL and the optimal antibody dilution at 1:200, the cutoff value distinguishing negative and positive serum samples was 0.986. The sensitivity test indicated that this rabbit pAb had a maximum dilution of 218 within the assay range, did not cross-react with BHV-1, BVDV, BRV, and BRSV positive serum samples, and shown great specificity. The developed iELISA method and commercial kit were used to test 58 bovine serum samples, and the concordance rate was 94.83%. In summary, we have developed a cost-efficient and precise iELISA method based on N protein that serves as a useful diagnostic tool for BCoV in clinical samples and epidemiological research.